ANALISIS FAKTOR YANG MEMPENGARUHI PARTISIPASI PEKERJA PEREMPUAN PADA SEKTOR INFORMAL DI DESA LALANGLINGGAH KABUPATEN TABANAN - I Gede Putra Widhi Guna Dharma; Ni Nyoman Yuliarmi (E-Jurnal Ekonomi Pembangunan, 2024)
Lalanglinggah Village is a tourist village located in the Selemadeg Barat District, Tabanan Regency. The agricultural sector dominates the livelihood of the residents of Lalanglinggah Village. The percentage of female labor force participation in this sector is the highest compared to male labor force participation. The high participation of female workers provides an insight and understanding that the majority of women in Indonesia (especially in rural areas) are driven to enter the labor market due to family economic pressures. Based on the phenomenon described, the purpose of this research is to determine the simultaneous and partial influence of age, education, husband's income, and the number of dependents on the participation of female workers in the informal sector in Lalanglinggah Village. In this research, the sample consists of 85 female workers, selected using accidental sampling method. This research employs inferential analysis techniques, specifically multiple linear regression analysis, with the assistance of SPSS software. The results obtained show that age, education, husband's income, and the number of dependents simultaneously have a significant influence on the participation of female workers in the informal sector in Lalanglinggah Village. Partially, the variables of age, education, and the number of dependents have a positive and significant impact, while the husband's income variable has a negative and significant impact. keyword: Informal workers, Age, Education, Husband's income, Number of dependents